Estudo químico de Erythricium salmonicolor, sua interação com a bactéria Xanthomonas citri e síntese de complexos antimicrobianos - Pinto, Luciano da Silva (Universidade Federal de São Carlos, 2022)
CHEMICAL STUDY OF Erythricium salmonicolor, ITS INTERACTION WITH THE BACTERIA Xanthomonas citri AND SYNTHESIS OF ANTIMICROBIAL COMPLEXES. The search for bioactive natural products has been increasingly important in the world scenario of disease control, whether pathogens or phytopathogens. The microorganisms that plague Brazilian cultures have developed resistance mechanisms in the face of many chemical controls, requiring a constant search for alternatives to overcome these challenges. Thus, understanding how these organisms develop in nature in their pathogenicity process with their host plants has been a successful approach in the development of prototypes of new antimicrobials. In this work, the chemical study of the fungus Erythricium salmonicolor was carried out by techniques such as CC, HPLC-DAD, HPLC-UV and the characterization of the chemical composition using the UPLC-HRMS MS/MS and RMN-1D and 2D techniques that resulted in substances 1- 34. In addition, the study of the growth curve of this fungus in PDA medium was carried out, analyzing the extracts by GC-MS and organizing the information with the aid of PCA analysis (Principal Component Analysis) and it was possible to verify that the ideal period for the microorganism was cultured for nine days and substances from these extracts 44-60 were identified in comparison with the spectra deposited in the NIST library with the book Adams. Also, to determine the biotechnological potential of the fungus, it was submitted to the study of biotransformation of the substrate rutin in a poor medium (Czapek) which yielded the biotransformation product 21. Finally, the complexation of the ligands rutin, naringin and vanillic acid with metals copper II, zinc II and iron II, which are characterized by NMR-1D, 2D and mass spectrometry, in addition to being subjected to the inhibitory concentration test (MIC) against the bacterium Xanthomonas citri where it was found that the complex of naringin with zinc was the most active having a MIC of ~200 µM.
Chemical study of Erythricium salmonicolor, its interaction with the bacteria Xanthomonas citri and synthesis of antimicrobial complexes
Keywords: Erythricium salmonicolor; Metabolômica; Complexos; Xanthomonas citri; Ácido fusárico; CIENCIAS EXATAS E DA TERRA::QUIMICA